1976
DOI: 10.1093/bja/48.12.1143
|View full text |Cite
|
Sign up to set email alerts
|

Pancuronium Bromide: An Indirect Sympathomimetic Agent

Abstract: In the dog, pancuronium 0.2 mg/kg increased left ventricular systolic pressure and systemic arterial pressure, but did not change central venous pressure. Repeated doses produced diminishing responses and eventually no change in arterial pressure. After tachyphylaxis was established, a pressor response to pancuronium could be induced by an i.v. infusion of noradrenaline. Desipramine, a noradrenaline blocking agent, prevented the restoration of the pressor effect of noradrenaline. Guanethidine and reserpine abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

1979
1979
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(19 citation statements)
references
References 10 publications
1
17
0
1
Order By: Relevance
“…d-Tubocurarine is known to cause histamine release and sympathetic ganglion blockade (4). As opposed to these effects, pancuronium has been shown to induce adrenergic transmitter release from the postganglionic nerve endings (2). Furthermore, at least under thiamyal anesthe-sia, pancuronium induces a significant rise in free epinephrine concentration (17).…”
Section: Discussionmentioning
confidence: 99%
“…d-Tubocurarine is known to cause histamine release and sympathetic ganglion blockade (4). As opposed to these effects, pancuronium has been shown to induce adrenergic transmitter release from the postganglionic nerve endings (2). Furthermore, at least under thiamyal anesthe-sia, pancuronium induces a significant rise in free epinephrine concentration (17).…”
Section: Discussionmentioning
confidence: 99%
“…The latter study and the present investigation also demonstrated that pancuronium alone, at concentrations up to 5 x 10-M, elicited no contractile activity in the vas, a preparation which responds to indirect sympathomimetic amines. Thus the noradrenaline-releasing effect of pancuronium, seen in the dog in vivo by Domenech et al (1976) was not evident in the rat tissues studied in vitro.…”
Section: Interactions Between Pancuronium and Cocainementioning
confidence: 78%
“…It is possible that pancuronium does exhibit weakly some properties of 17 fl-oestradiol because this would explain the depression of the response of the vas to St 91 seen after pancuronium and the depression of the response to NA seen on administration of pancuronium after cocaine (see Figures lb and 2a). The NA supersensitivity of vascular smooth muscle caused by pancuronium is probably of greater significance to the anaesthetist than the extensively studied effects on the heart (Saxena & Bonta, 1970;Ivankovich et al, 1975;Domenech et al, 1976). Fuzzey & Edwards (1971) examined the effect of pancuronium on heart rate, arterial blood pressure and calf muscle blood flow in anaesthetized patients with peripheral vascular disease.…”
Section: Interactions Between Pancuronium and Cocainementioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence suggests that potentiation of the cardiac sympathetic component might also be involved (Ivankovitch, Militech, Albrecht & Zahed, 1975;Domenech, Garcia, Sasiain, Loyola & Oroz, 1976;Docherty & McGrath, 1977;1978). If so, this might provide a more satisfactory explanation than has, so far, been available for the clinical observations since vagal inhibition, alone, should not produce any considerable tachycardia without the presence of a sympathetic component and since tachycardia to pancuronium can still occur after atropine (Stoelting, 1972).…”
Section: Introductionmentioning
confidence: 99%